ANALYSIS OF THE INFLUENCE OF SUBANG EXIT TOLL ON CHANGES IN COMMERCIAL LAND USE AND TRAFFIC VOLUME IN OTTO ISKANDARDINATA ROAD CORRIDOR, SUBANG DISTRICTA - Andika Ahsana (Journal of Development and Integrated Engineering, 2022)
The development of highway infrastructure and Exit Tolls is very important for regional development. The existence of toll road infrastructure and Exit tolls provides easy access by land route so it is expected to have an impact on accelerating regional economic growth. Since the construction of the Exit Toll access in Subang City, the area around the Exit Toll has become an important area for regional development, especially community economic activities such as trade, industry, and public services. Over time, the area around the Subang Toll Exit has developed into a center of commercial activity marked by changes in land use along the corridor of Jalan Otto Iskandardinata. This study aims to analyze the impact of land use change and its relationship to traffic volume that has occurred along the Jalan Otto Iskandardinata corridor since the opening of the Subang Toll Exit access. Land use change analysis is carried out by comparing satellite imagery data obtained from Google Earth and through field surveys. The correlation with traffic volume was obtained through linear regression analysis with land use change as the dependent variable and vehicle activity in the road corridor as the independent variable. The results show that land use changes that occur along the corridor of Jalan Otto Iskandardinata Subang are dominated by commercial land uses. The change in land use also has an impact on changing the visual image of the road corridor.